투과성 해안구조물 내-외부 파동장의 수리특성에 관한 수치모의 - 차종호(JONG-HO CHA); 윤한삼(HAN-SAM YOON); 류청로(CHEONG-RO RYU); 강윤구(YOON-KOO KANG) (Han-guk haeyang gonghak hoeji (Online), 2008)
This study investigated interactions between the internal-external wave field of a permeable coastal structure consisting of rubble. The study examined the application criteria of an existing numerical model (CADMAS-SURF V.4.0) and proposed a modified method to provide reasonable results. In particular, the study focused on and emphasized the water surface profiles in front of a structure, wave run-up/run-down on a slope, and internal water level fluctuations due to the drag coefficient and porosity of a rubble mound structure. In conclusion, the result show that when the vertical fluctuations of the internal water levels in permeable coastal structures exhibited high-quality representation. Sane responses can be seen for wave run-up/run-down characteristics on its slopes. This study investigated interactions between the internal-external wave field of a permeable coastal structure consisting of rubble. The study examined the application criteria of an existing numerical model (CADMAS-SURF V.4.0) and proposed a modified method to provide reasonable results. In particular, the study focused on and emphasized the water surface profiles in front of a structure, wave run-up/run-down on a slope, and internal water level fluctuations due to the drag coefficient and porosity of a rubble mound structure. In conclusion, the result show that when the vertical fluctuations of the internal water levels in permeable coastal structures exhibited high-quality representation. Sane responses can be seen for wave run-up/run-down characteristics on its slopes. KCI Citation Count: 0